Celio Calcagnini (1479-1541) - Breen, Quirinus (Church history, 1952)
Celio Calcagnini's active career falls in a period marked by many men of note and by a number of significant events. He touched some of these directly or indirectly. He was involved in an imperial and in a papal war, in an imperial election, in the controversy stirred up by Luther, in the divorce question precipitated by Henry VIII. He fanned into flame the conflict over the imitation of Cicero. He took an interest in Egyptian hieroglyphics. Independently of Copernicus, Calcagnini made a curious and not altogether ridiculous contribution toward creating an attitude of mind favorable to the new conception of the solar system for which Copernicus was to become famous. He was personally acquainted with the painter Raphael, with Jovius, with Manardi the physician, with Ziegler, the poet Ariosto, the humanist Erasmus. In his home-town of Ferrara he enjoyed a place of honor as university professor, as apostolic prothonotary, as an excellent dinner host. He was considered to be one of the most learned men of Italy. Yet his importance was always that of a bridesmaid rather than of a bride. It has its uses, however, to look at a wedding from a bridesmaid's angle. To see an era reflected in the career of a minor actor may prove rewarding.